(3HMhQ GdHOGFY GdeMJhjI Ydi OQQ GdCTYGQ GdeUWahjIs - (3eUWai (B((3Ch eMeO eUWai(B) (3Hf eMeO aGVd Hf eMeO Cejf GdTfbjWj Gdbdbej, CHh GdCfhGQ, GdedbH HeGA GdYjfjf, J (B1328 (3g` s
(3ChdgG (B:s
(3GeG HYO ajbhd eGA GdYjfjf Hf GdYJjb (B:(3Efi deG fXQJ ajeG GdCejQ GdeDefjf SjOi eMeO GdeUWai ef MSf UfGYI GdcdGe hLhOI HQGYI GdfXJe s
(3BNQgG (B:s
(3ai GdfUQ hGdJejcf ai EeQJg hbQI GdYjfjf ai fSHJg hdYWg ai GdYR GbUi cd QShd HLGg LOg fHjfG GdQShd Cced dg efc GdUGOQI hGdSdGe hced HLGgg dfG GdeQGe s
(3OjhGf TYQ GdCHMQ GdeYfjI ai GdCeOGM GdYjfjI GdeSei HOjhGf GHf eGA GdYjfjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B243 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1353) s
Keywords: (3GdCOHs